2017
DOI: 10.1007/s10620-017-4788-3
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Tyrosine Tyrosine 3-36 Reduces Meal Size and Activates the Enteric Neurons in Male Sprague–Dawley Rats

Abstract: The gastrointestinal tract may contain sites of action regulating MS reduction by PYY 3-36.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Activation of the DVC and the enteric neurons as manifested by increased Fos-LI in response to other satiety gut peptides e.g., S CCK-8 (Gulley et al, 2005a;Sayegh andRitter, 2000, 2003;Sullivan et al, 2007), glucagon like peptide-1 (GLP-1) (Washington et al, 2010), gastrin releasing peptide-29 (GRP-29) and peptide tyrosine tyrosine (PYY) (Newman et al, 2017) has been documented prior to this report. The current study demonstrated that NS CCK-8 also increases Fos-LI in these neurons.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Activation of the DVC and the enteric neurons as manifested by increased Fos-LI in response to other satiety gut peptides e.g., S CCK-8 (Gulley et al, 2005a;Sayegh andRitter, 2000, 2003;Sullivan et al, 2007), glucagon like peptide-1 (GLP-1) (Washington et al, 2010), gastrin releasing peptide-29 (GRP-29) and peptide tyrosine tyrosine (PYY) (Newman et al, 2017) has been documented prior to this report. The current study demonstrated that NS CCK-8 also increases Fos-LI in these neurons.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, the actions of NS CCK-8, possibly including reduction of food intake, may be peripheral/local i.e., gastrointestinal. Others (Calingasan et al, 1992;Cox et al, 1996;Smith et al, 1988) and we (Mhalhal et al, 2017b;Newman et al, 2017;Sayegh et al, 2015;Washington et al, 2016b) have shown that the gastrointestinal tract is a potential site of action for reduction of food intake by S CCK-8, GRP-29 and GLP-1, (Mhalhal et al, 2017a(Mhalhal et al, , 2018Washington et al, 2014), because intra-arterial infusions of S CCK-8 (0.05 nmol/kg) in the cranial mesenteric artery, which supplies the small intestine, but not ip injections, reduced food intake (Mhalhal et al, 2017a,b;Sayegh et al, 2015;Washington et al, 2016a,b). In addition, interrupting the enteric neurons utilizing a duodenal myotomy procedure also attenuated reduction of food intake by the same peptide (Lateef et al, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…Intraperitoneal injection of PYY and NPY inhibit fecal pellet output per hour and inhibited high-amplitude distal colonic contractions and cholinergic-stimulated propulsive colonic motor function ( 34 ). They can increase cFOS activity in enteric neurons and exert powerful inhibitory effects on myenteric neurons of the descending colon ( 33 , 36 ). In proximal part of the GI tract, exogenous PP stimulates mouse gastric motor activity, by activating gastric enteric excitatory neurons releasing acetylcholine (Ach) and tachykinins ( 35 ) (Table 1 ).…”
Section: Peptides Modulating Ens Neuronsmentioning
confidence: 99%